2016
DOI: 10.3389/fpls.2016.01685
|View full text |Cite
|
Sign up to set email alerts
|

Apple F-Box Protein MdMAX2 Regulates Plant Photomorphogenesis and Stress Response

Abstract: MAX2 (MORE AXILLARY GROWTH2) is involved in diverse physiological processes, including photomorphogenesis, the abiotic stress response, as well as karrikin and strigolactone signaling-mediated shoot branching. In this study, MdMAX2, an F-box protein that is a homolog of Arabidopsis MAX2, was identified and characterized. Overexpression of MdMAX2 in apple calli enhanced the accumulation of anthocyanin. Ectopic expression of MdMAX2 in Arabidopsis exhibited photomorphogenesis phenotypes, including increased antho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
(70 reference statements)
0
22
0
Order By: Relevance
“…43 Differences were considered statistically significant when P <0.05 and P <0.01. The results were analyzed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…43 Differences were considered statistically significant when P <0.05 and P <0.01. The results were analyzed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…But the detailed molecular mechanism awaits to be elucidated [60]. A number of studies also have indicated that MAX2 contributes to plant responses to both biotic and abiotic stresses through modulation of the ABA signaling pathway and that MAX2 gene expression can be influenced by ABA treatment [42, 75, 88]. Bu et al showed that MAX2 expression was suppressed to about 50% after Arabidopsis seedlings were treated with 50 μM ABA for 6 h [42].…”
Section: Discussionmentioning
confidence: 99%
“…Apple ( Malus domestica ) is an important commercial fruit crop, and its production is highly affected by environmental factors, especially light [ 29 , 30 ]. PIFs play a central role in adapting plants to different light conditions; however, identification and functional analysis of PIFs in apples have not been systematically investigated, except MdPIF1 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%